DAMPAK PENGELUARAN PEMERINTAH DAN WISATAWAN SERTA INVESTASI SWASTA TERHADAP KINERJA PEREKONOMIAN BALI: SUATU SIMULASI MODEL SOCIAL ACCOUNTING MATRIX - MADE ANTARA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2000)
Bali's economic development is focused on agriculture, tourism and industry as thefirst priority. While other part of the Indonesia economy were suffering severely due toeconomic down turn since the middle of 1997, Bali's economy seems less affected. Theperformance of Bali's economy was analyzed employing 1996 Social Accounting Matrix(SAM), constructed based on 55x55 accounts. It is assumed that this 1996 SAM couldrepresent the present situation of Bali's economy.The impact of increased allocation of expenditures for economic infrastructure,without increased in total government expenditure, on the performance of Bali’s economywas relatively low. While increased allocation of expenditure on social infrastructure orpublic services without increase in total government expenditure would deterioratesubstantially the performance of Bali’s economy.Maintaining the government expenditure for development as in 1996 levels, but anincrease in the expenditure of tourists or private investment, would enhanced the performanceof Bali’s economy. Even a decline in government expenditure could be compensated by anincrease in tourist expenditure or private investment, suggesting that government expenditurewas not the main sources of economic growth.However, an increase in tourist expenditure without effort to increase the governmentexpenditure would affect the income distribution among household group towards moreinequality. But, increase tourist expenditure as well as government expenditure wouldpromote better income distribution.